OPTIMALISASI PERAN PEMERINTAH DAERAH DALAM PELAKSANAAN SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) (Studi pada Pemerintah Kabupaten Tuban): population, information system of population administration, e-government - Anggaini, Niken Lastiti Veri (JAMAK, 2016)
Information System of Population Administration (SIAK) is a system for the collection, processing and presentation of Population Data accurately in order to produce proper population information for development and public services It consits of Population Registration and Civil Registration by using Information Technology. This study aimed to describe and analyze the optimalization of local government role in the implementation of SIAK and the factors that influence the role optimalization. The method used is qualitative method by applying some steps in collecting the data, such as observation, documentation, and conducting some interviews to the field informant, which is obtained through Key Informant. The result of the research showed that thera are three way to opimalize role of local government in implementation SIAK, thai is Empowerment the management officer SIAK, the provision of data recording place on population and development population data base. The influence factors consits of the population itself, human resource capacity, and infrastructure